Changes on lived and coping practice experiences among traumatic brain injury survivors and caregivers in Malaysia - Abdul Rashid, Nor'ain (2022)
Traumatic brain injury (TBI) imparts a long-term effect on the survivors’ lives. Given those changes, survivors apply several coping practices to continue their activities of daily living. Limited studies have been conducted in a Malaysian setting related to changes in the lived experiences and coping practices of TBI survivors and caregivers. This study also discusses the gap in the International Classification of Functioning, Disability and Health (ICF) Model, which contains only a limited assessment of the emotional changes in disabled people, especially TBI survivors. The purpose of this study was to understand the changes in the lived experiences and coping practices of post-TBI survivors and their caregivers. A hermeneutic phenomenology approach was applied in this study. Participants were recruited at a rehabilitation hospital in Malaysia after approval had been obtained from the National Medical Research Registry (NMRR), Jawatan Kuasa Etika UPM (JKEUPM) and the hospital ethics board, while consent was obtained from the participants. A total of 20 participants were involved, of which 14 were TBI survivors and six were caregivers of survivors. Data collection was done using semi-structured interviews with both TBI survivors and their caregivers. Other data collection methods were also used, such as field notes, a reflective journal and the story completion technique. All the raw data collected using these methods were triangulated to obtain rich and thick description. Thematic analysis was applied in the data analysis process using Nvivo software version 1.0. Two themes were identified for changes in lived experiences as described by the participants: direct and indirect changes. The former was defined as changes in lived experiences that survivors had directly undergone after an injury; these changes could be identified by others and included physical changes, cognitive changes, behavioural changes, post-injury trauma and fatigue. Indirect changes were defined as changes in survivors’ lived experiences that people could not see directly, although these changes affected the survivors in terms of emotions, stigma, role changes and financial difficulties. In regard to coping practices experiences, two themes were described by the participants: problem-focused and emotional-focused coping. The former refers to coping with the direct changes that affected the participants, while the latter refers more to addressing emotions and finding support from others. Some participants had withdrawn from society and avoided taking any risks because of the post-injury changes in lived experiences. TBI survivors often have a long-term recovery process that might be influenced by internal and external problems. To assist and improve the care of TBI survivors throughout their recovery period, understanding their changes in lived experiences and coping practices is an important aspect that healthcare providers and family members must recognise